Role of Regulatory T Cells in Disturbed Immune Homeostasis in Patients With Chronic Obstructive Pulmonary Disease - Hou, Jia; Sun, Yongchang (Frontiers in Immunology, 2020)
Chronic obstructive pulmonary disease (COPD) is a complex chronic disease in which T cell-mediated pulmonary inflammation has been shown to play a key role. Accumulating evidence shows that COPD has many of the characteristics of an autoimmune response. An adaptive immune response directed against lung self-antigens, which are released during the initial innate inflammatory response and are triggered by constant exposure to cigarette smoke and epithelial injury, drives the persistent inflammatory response found in smokers. The development and severity of adaptive inflammation depend on the level of tolerance to self-antigens. For these reasons, the effect of regulatory T (Treg) cells on adaptive immunity in COPD patients is of particular interest and could be targeted therapeutically. The disturbance in immune homeostasis caused by changes in the number or function of Treg cells, which is related to cigarette smoke exposure, may be of importance in understanding the development and progression of COPD.